Value of long-chain polyunsaturated fatty acids for infants' health and development - Д. О. Добрянський; Т. К. Знаменська; О. В. Воробйова; І. І. Воробйова (Publishing House TRILIST, 2019)
The level of intake of essential polyunsaturated fatty acids (PUFAs) in pregnant, newborns and young children affects the quality of growth, state of the cardiovascular system, neurological and immune functions in childhood and later life. Child receives PUFAs through the placenta and with the mother's milk, and therefore the peculiarities of the mother's diet affect the supply of these fetal acids, as well as their content in breast milk. In the vast majority of countries with limited resources the use of docosahexaenoic and arachidonic acids in pregnant women, infants and young children may be significantly lower than recommended. Numerous randomized, controlled studies examined the effect of additional PUFAs consumption during pregnancy, lactation and postnatal period on physical, psychomotor, speech and mental development of children, their behavior, visual acuity, cardiovascular function and immune responses. Available data suggests that the additional consumption of long-chain PUFAs for children on breast or artificial feeding does not improve visual acuity, physical development or speech development. Additional n-3 PUFA may also affect some aspects of motor development, cardiovascular health, behavior and immunity with a more positive effect on breast-feeding children than children fed with milk nutrition. There is also evidence that an additional use of n-3 long-chain PUFA, in particular docosahexaenoic acid and eicosopentaenoic acid may reduce the incidence or severity of the most commonly occurring diseases specific to premature infants. In 2013, the European Food Safety Authority considered adequate daily intake levels of double-stranded PUFAs for most infants and young children to be adequate: 100 mg of docosahexaenoic acid and 140 mg of arachidonic acid from birth to 6 months, 100 mg of docosahexaenoic acid from 6 to 24 months and 250 mg eykozopentaenovoy + docosahexaenoic acid later than 24 months of age.